PENYULUHAN PENINGKATAN KESADARAN MASYARAKAT DALAM PENGELOLAAN SAMPAH ORGANIK MELALUI PROGRAM BANK SAMPAH - Haholongan, Rutinaias; Achmad Putra Setiawan; Muhammad Fadhyl Alim; Rahel Alexcandra; Chintya Hafidz Musdailfah (CV SWA Anugerah, 2024)
This research aims to develop an organization for community service which is an organic waste management program carried out at the PKK (Family Welfare Empowerment). What is being implemented in the region (PEGANGSAAN) aims to reduce the volume of waste that ends up in landfills (TPA) and improve the quality of the environment. This activity also involves making compost, outreach to the community. This program was carried out to increase public awareness of the importance of managing organic waste independently. Apart from that, this method has proven to be effective in processing organic waste into high quality compost in a relatively short time. Apart from that, this group has also succeeded in utilizing compost products to develop value-added products, such as liquid organic fertilizer and planting media and the production of the resulting compost can also be used to fertilize plants in the surrounding environment